The Influence Of The Recruitment And Selection Process On Employee Work Quality Mediated By Competence At PT Arjuna Sejahtera Bersama - Mawan Mawan; Anna Wulandari; Sarwo Edy (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to determine The Influence Of The Recruitment And Selection Process On Employee Work Quality With Competence as Mediation At PT Arjuna Sejahtera Bersama. Respondents of this study were 70 respondents and this study used a quantitative approach with the SmartPLS 3.0 data processing application. The results of this study found that 1. Recruitment Process has no significant effect on competence, 2. Selection process has a significant effect on competence, 3. Recruitment Process has no significant effect on employee work quality, 4. Selection process has a significant effect on employee work quality, 5. Competence has a significant effect on employee work quality.